The SpaTemp cohort: 168 nondysplastic Barrett's esophagus surveillance patients with and without progression to early neoplasia to evaluate the distribution of biomarkers over space and time. Issue 3 (18th September 2020) - Frei, N F; Konté, K; Duits, L C; Klaver, E; Ten Kate, F J; Offerhaus, G J; Meijer, S L; Visser, M; Seldenrijk, C A; Schoon, E J; Weusten, B L A M; Schenk, B E; et al.
Summary: The ReBus cohort is a matched nested case–control cohort of patients with nondysplastic (ND) Barrett's esophagus (BE) at baseline who progressed (progressors) or did not progress (nonprogressors) to high-grade dysplasia (HGD) or cancer. This cohort is constructed using the most stringent inclusion criteria to optimize explorative studies on biomarkers predicting malignant progression in NDBE. These explorative studies may benefit from expanding the number of cases and by incorporating samples that allow assessment of the biomarker over space (spatial variability) and over time (temporal variability). To (i) update the ReBus cohort by identifying new progressors and (ii) identify progressors and nonprogressors within the updated ReBus cohort containing spatial and temporal information. The ReBus cohort was updated by identifying Barrett's patients referred for endoscopic work-up of neoplasia at 4 tertiary referral centers. Progressors and nonprogressors with a multilevel (spatial) endoscopy and additional prior (temporal) endoscopies were identified to evaluate biomarkers over space and over time. The original ReBus cohort consisted of 165 progressors and 723 nonprogressors. We identified 65 new progressors meeting the same strict selection criteria, resulting in a total number of 230 progressors and 723 matched nonprogressors in the updated ReBus cohort. Within the updated cohort, 61 progressors and 107 nonprogressors (mean age 61 ± 10 years) with a spatial endoscopy (median level 3 [2–4]) were identified. 33/61 progressors and 50/107 nonprogressors had a median of 3 (2–4) additional temporal endoscopies. Our updated ReBus cohort consists of 230 progressors and 723 matched nonprogressors using the most strict selection criteria. In a subgroup of 168 Barrett's patients (the SpaTemp cohort), multiple levels have been sampled at baseline and during follow-up providing a unique platform to study spatial and temporal distribution of biomarkers in BE.